The Volatilomic Footprints of Human HGC-27 and CLS-145 Gastric Cancer Cell Lines - Leiherer, Andreas; Ślefarska, Daria; Leja, Marcis; Heinzle, Christine; Mündlein, Axel; Kikuste, Ilze; Mezmale, Linda; Drexel, Heinz; Mayhew, Chris A.; Mochalski, Paweł (Frontiers in Molecular Biosciences, 2021)
The presence of certain volatile biomarkers in the breath of patients with gastric cancer has been reported by several studies; however, the origin of these compounds remains controversial. In vitro studies, involving gastric cancer cells may address this problem and aid in revealing the biochemical routes underlying the production and metabolism of gastric cancer volatile indicators. Gas chromatography with mass spectrometric detection, coupled with headspace needle trap extraction as the pre-concentration technique, has been applied to map the volatilomic footprints of human HGC-27 and CLS-145 gastric cancer cell lines and normal Human Stomach Epithelial Cells (HSEC). In total, twenty-seven volatile compounds are found to be associated with metabolism occurring in HGC-27, CLS-145 and HSEC. Amongst these, the headspace concentrations of twelve volatiles were found to be reduced compared to those above just the cultivating medium, namely there was an observed uptake of eight aldehydes (2-methylpropanal, 2-methyl-2-propenal, 2-methylbutanal, 3-methylbutanal, hexanal, heptanal, nonanal, and benzaldehyde), three heterocyclic compounds (2-methyl-furan, 2-ethyl-furan and 2-pentyl-furan) and one sulphur-containing compound (dimethyl disulphide). For the other fifteen volatiles, the headspace concentrations above the healthy and cancerous cells were found to be higher than those found above the cultivating medium, namely the cells were found to release three esters (ethyl acetate, ethyl propanoate and ethyl 2-methylbutyrate), seven ketones (2-pentanone, 2-heptanone, 2-nonanone, 2-undecanone, 2-tridecanone, 2-pentadecanone, 2-heptadecanone), three alcohols (2-methyl-1-butanol, 3-methyl-1-butanol, 2-ethyl-1-hexanol), one aromatic compound (toluene), and one sulphur containing compound (2-Methyl-5-(methylthio) furan). In comparison to HSEC, HGC-27 cancer cell lines were found to have significantly altered metabolism, manifested by an increased production of methyl ketones containing an odd number of carbons. Amongst these species, three volatiles were found exclusively to be produced by this cell line, namely 2-undecanone, 2-tridecanone and 2-heptadecanone. Another interesting feature of the HGC-27 footprint is the lowered level of alcohols and esters. The CLS-145 cells exhibited less pronounced changes in their volatilomic pattern compared to HSEC. Their footprint was characterized by the upregulated production of esters and 2-ethyl-hexanol and downregulated production of other alcohols. We have therefore demonstrated that it is possible to differentiate between cancerous and healthy gastric cells using biochemical volatile signatures.